Security-enhanced watermark embedding and transmission based on synchronized chaotic semiconductor lasers - Wang, Jun; Tang, Xi; Wang, Fei; Lin, Xiaodong; Zheng, Qiulan; Xia, Guangqiong; Wu, Zhengmao; Deng, Tao (Nonlinear dynamics, 2023)
In this paper, we propose and numerically demonstrate a chaotic watermarking encryption and secure transmission scheme based on two synchronized response lasers (RLs) subject to identical injection from a driving laser (DL). In this proposed system, the chaotic signal from DL can be optimized after passing through a phase modulator and a dispersion component, then the chaotic signal with large bandwidth and low time delay signature is obtained. Simultaneously injecting this chaotic signal into two identical RLs, high-quality chaos synchronization between two RLs can be realized. Both synchronized chaotic signals are, respectively, divided into two parts. One is used to generate shared keys required by the watermarking encryption, and the other is used as chaotic carrier to realize the secure message transmission. After introducing the synchronized optical chaos into the watermarking encryption algorithm, the normalized correlation of the extracted watermark without long-distance transmission is 0.9554 and can still maintain above 0.9 over 200 km transmission fiber. The message transmission and watermark extraction have good robustness to the fiber parameter mismatches, and excellent performances can be maintained even within 20% mismatches range. In our method, synchronized high-quality optical chaotic signals from two RLs are used to watermark embedding and transmission, and double encryption can be realized, which can open a new path for future high-speed and security-enhanced watermark embedding and transmission.